Elevated Homocysteine and Carotid Plaque Area and Densitometry in the Northern Manhattan Study - Alsulaimani, Sara; Gardener, Hannah; Elkind, Mitchell S.V.; Cheung, Ken; Sacco, Ralph L.; Rundek, Tatjana (Stroke (1970), 2013)
Studies have linked elevated total homocysteine (tHcy) levels to atherosclerotic carotid plaque development, but data are limited to predominantly white populations. We examined the association between tHcy and carotid plaque burden and morphology in a multiethnic cohort. In the Northern Manhattan Study, we conducted a cross-sectional analysis among 1327 stroke-free subjects (mean age, 66 ± 9; 41% men; 19% black; 62% Hispanic; 17% white) with serum tHcy and ultrasonographic assessment of plaque morphology measured by gray-scale median (GSM) and total plaque area (TPA). GSM and TPA were examined in 4 categories. High and low GSM categories were considered echodense and echolucent plaque, respectively, and compared with no plaque. Logistic regression models were used to assess the associations of tHcy with GSM and TPA adjusting for demographics, vascular risk factors, renal insufficiency, and B(12) deficiency. The mean tHcy was 9.4 ± 4.8 µmol/L (median=8.6). The prevalence of carotid plaque was 57% (52% among Hispanics, 58% black, and 70% white). Among those with plaque, the mean TPA was 20.3 ± 20.6 mm(2) (median=13.6) and mean GSM 90.9 ± 28.5 (median=93.0). The top 2 tHcy quartiles (versus quartile 1) had an elevated risk of having either echolucent plaque (tHcy Q3, odds ratio [OR]=1.8; [95% confidence interval CI 1.2-2.8]; tHcy Q4, OR=1.9 [95% CI 1.2-3.1]) or echodense plaque (tHcy Q3, OR=1.7 [95% CI, 1.1-2.7]; tHcy Q4, OR=1.9 [95% CI, 1.2-3.2]). The top 2 tHcy quartiles were also more likely to be in the highest TPA category (tHcy Q3, OR=1.8 [95% CI, 1.1-3.0]; tHcy Q4, OR=2.2 [95% CI, 1.3-3.7]). In this population-based multiethnic cohort, elevated tHcy was independently associated with plaque morphology and increased plaque area, subclinical markers of stroke risk.